High-Throughput Generation of P. falciparum Functional Molecules by Recombinational Cloning - Aguiar, João Carlos; LaBaer, Joshua; Blair, Peter L.; Shamailova, Victoria Y.; Koundinya, Malvika; Russell, Joshua A.; Huang, Fengying; Mar, Wenhong; Anthony, Robert M.; Witney, Adam; Caruana, Sonia R.; Brizuela, Leonardo; et al. (Genome Research, 2004)
Large-scale functional genomics studies for malaria vaccine and drug development will depend on the generation of molecular tools to study protein expression. We examined the feasibility of a high-throughput cloning approach using the Gateway system to create a large set of expression clones encoding Plasmodium falciparum single-exon genes. Master clones and their ORFs were transferred en masse to multiple expression vectors. Target genes (n = 303) were selected using specific sets of criteria, including stage expression and secondary structure. Upon screening four colonies per capture reaction, we achieved 84% cloning efficiency. The genes were subcloned in parallel into three expression vectors: a DNA vaccine vector and two protein expression vectors. These transfers yielded a 100% success rate without any observed recombination based on single colony screening. The functional expression of 95 genes was evaluated in mice with DNA vaccine constructs to generate antibody against various stages of the parasite. From these, 19 induced antibody titers against the erythrocytic stages and three against sporozoite stages. We have overcome the potential limitation of producing large P. falciparum clone sets in multiple expression vectors. This approach represents a powerful technique for the production of molecular reagents for genome-wide functional analysis of the P. falciparum genome and will provide for a resource for the malaria resource community distributed through public repositories.